Use of the Strengths and Difficulties Questionnaire in child and school health services among children aged 4 and 6 years in Southern Norway: clinical considerations - Eirin Mølland; Kristin Haraldstad; Eirik Abildsnes; Åshild Tellefsen Håland; Unni Mette Stamnes Köpp; Liv Fegran; Thomas Westergren (BMC Pediatrics, 2023)
Abstract Background Parent reported mental health can be assessed by the Strengths and Difficulties Questionnaire (SDQ). Currently, Norwegian norms for parent-reported SDQ do not exist, whereas Swedish, Danish, and United Kingdom (UK) norms have been published. We aimed to (1) describe parent-reported SDQ among children aged 4 and 6 years in Southern Norway, (2) evaluate empirical cutoff values within the context of the Starting RightTM project in relation to the Swedish, Danish, and UK cutoffs, and (3) evaluate the representativeness of the study sample with regard to parental socioeconomic status. Methods This study included parent-reported observations for 665 children (63% consent rate). Means and standard deviations were calculated for the domains of SDQ, and gender differences were assessed. Based on the Swedish, Danish, and UK cutoffs and the 80th and 90th percentile cutoff values within the study, we calculated the total number of children with borderline and abnormal scores. Results Boys had higher mean total difficulties (7.3 vs 5.6) and impact scores (0.3 vs 0.1) and lower prosocial scores (8.3 vs 8.8) than girls. The differences in means were largest in the case of externalizing symptoms (5.0 vs 3.6) and hyperactivity subscore (3.2 vs 2.3). Using the UK cutoff values, 28 and 25 children had borderline and abnormal total difficulties scores, respectively. The corresponding numbers using the within study or Scandinavian cutoff values were 84–99 and 54–79, respectively. Overall, our study sample was well representative of the target population. Conclusions Our findings consistently indicated that girls had better SDQ scores than boys among children aged 4 and 6 years. Fewer children would be identified as having mental health difficulties using the UK cutoff values than using the Scandinavian age- and gender-relevant cutoff values.